Dysregulation of the axonal trafficking of nuclear‐encoded mitochondrial mRNA alters neuronal mitochondrial activity and mouse behavior. Issue 3 (20th November 2013) - Kar, Amar N.; Sun, Ching‐Yu; Reichard, Kathryn; Gervasi, Noreen M.; Pickel, James; Nakazawa, Kazu; Gioio, Anthony E.; Kaplan, Barry B.; Sotelo‐Silveira, José R.; Holt, Christine E.
ABSTRACT Local translation of nuclear‐encoded mitochondrial mRNAs is essential for mitochondrial activity, yet there is little insight into the role that axonal trafficking of these transcripts play in neuronal function and behavior. Previously, we identified a 38 nucleotide stem‐loop structure (zipcode) in the 3' untranslated region of the Cytochrome C oxidase IV (COXIV) mRNA that directs the transport of a reporter mRNA to the axon of superior cervical ganglion neurons (SCG). Overexpression of a chimeric reporter mRNA with the COXIV zipcode competed with the axonal trafficking of endogenous COXIV mRNA, and led to attenuated axon growth in SCG neurons. Here, we show that exogenous expression of the COXIV zipcode in cultured SCG neurons also results in the reduction of local ATP levels and increases levels of reactive oxygen species (ROS) in the axon. We took advantage of this "competition" phenotype to investigate the in vivo significance of axonal transport of COXIV mRNA. Toward this end, we generated transgenic mice expressing a fluorescent reporter fused to COXIV zipcode under a forebrain‐specific promoter. Immunohistological analyses and RT‐PCR analyses of RNA from the transgenic mouse brain showed expression of the reporter in the deep layer neurons in the pre‐frontal and frontal cortex. Consistent with the in vitro studies, we observed increased ROS levels in neurons of these transgenic animals. A battery of behavioral tests on transgenic mice expressing the COXIV zipcode revealed an "anxiety‐like" behavioral phenotype, suggesting an important role for axonal trafficking of nuclear‐encoded mitochondrial mRNAs in neuronal physiology and animal behavior. © 2013 Wiley Periodicals, Inc. *Develop Neurobiol 74: 333–350, 2014